AXIOLOGICAL PRIORITIES IN STRUCTURE OF PERSONAL-PROFESSIONAL ORIENTATION OF TEACHERS INVOLVED IN INCLUSIVE EDUCATION - Galina Yurjevna Kozlovskaya (Вестник Северо-Кавказского федерального университета)
The article dwells on the issues related to the development of personal-professional orientation in teachers involved in inclusive education; value components of personal-professional readiness to work with disabled people in inclusive education, as such issues are discussed in in national and international pedagogic science.